2008
DOI: 10.1111/j.1524-4725.2008.34307.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Investigation of the Correlation between Histological and Clinical Effects of Infrared Fractional Resurfacing Lasers

Abstract: Greater densities of shallower damage columns at lower energies may better improve pigmentation, whereas deeper injuries, using higher energies and moderate densities, may better improve texture. This pilot study did not compare similar fluences and histologic damage between the two systems, and newer available systems allow for greater depth of penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…13,[15][16][17][18][19]23,[25][26][27][28][29][30][31] It has been demonstrated in the literature with FP in clinical-histologic correlation experiments that a greater depth of injury maximizes texture improvement, whereas a higher density of more superficial injuries maximizes improvement in pigmentation. [35][36][37] Recent histologic and ultrasound studies with AFP by our group at the settings reported herein have documented ablation into the mid-reticular dermis with stimulation of neocollagenesis and collagen remodeling. 35,36 Thus, the pattern of deep ablation into the reticular dermis and resultant stimulation of collagen contraction and synthesis likely accounts for its greater efficacy in tissue tightening and skin texture.…”
Section: Discussionmentioning
confidence: 87%
“…13,[15][16][17][18][19]23,[25][26][27][28][29][30][31] It has been demonstrated in the literature with FP in clinical-histologic correlation experiments that a greater depth of injury maximizes texture improvement, whereas a higher density of more superficial injuries maximizes improvement in pigmentation. [35][36][37] Recent histologic and ultrasound studies with AFP by our group at the settings reported herein have documented ablation into the mid-reticular dermis with stimulation of neocollagenesis and collagen remodeling. 35,36 Thus, the pattern of deep ablation into the reticular dermis and resultant stimulation of collagen contraction and synthesis likely accounts for its greater efficacy in tissue tightening and skin texture.…”
Section: Discussionmentioning
confidence: 87%
“…Extrapolating data from studies done for rhytides[2527] are not useful as the dose and depth required are less as compared to acne scars. Also, in rhytides,[101215] the periocular area is targeted, which is not the site for acne scars. Some studies employed a two-step procedure where the histology was done on ex vivo animal or ex vivo human model,[101215] and the clinical evaluation was done on the in vivo facial skin.…”
Section: Invasive (Histological) Assessment Of Fractional Lasermentioning
confidence: 99%
“…Also, in rhytides,[101215] the periocular area is targeted, which is not the site for acne scars. Some studies employed a two-step procedure where the histology was done on ex vivo animal or ex vivo human model,[101215] and the clinical evaluation was done on the in vivo facial skin. This is not scientifically replicable as there are differences in the tissue responses in different substrate models.…”
Section: Invasive (Histological) Assessment Of Fractional Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo animal model using pig skin has been used in some previous studies1,2, but porcine skin differs from human skin histologically and physiologically, including thickness, vascularity, and pH3. In addition, recent increases in the awareness of animal welfare and legal issues have raised the need for alternatives to animal models4.…”
Section: Introductionmentioning
confidence: 99%